Formulasi Strategi Manajemen Aset Dan Liabilitas (ALMA) Pada Perbankan - Darwis Darwis; Helmy Toatubun (Musamus University, Merauke Papua Indonesia., 2021)
This article discusses the problem of optimizing bank balance sheet structures through the management of assets and liabilities in banking institutions. By using descriptive analysis, this study explores the theoretical study approach of the application of Asset and Liability Management (ALMA) which is used by banks as a financial information management system formulation through the application of asset and liability management functions (ALMA) to maintain the balance of the assets and liabilities side of the bank's balance sheet. implemented by the Asset Liability Committee (ALCO) and ALCO Support Group (ASG). The results of this study, it is concluded that the operationalization of the functions of asset and liability management (ALMA) can optimize the balance sheet structure of banks in a competitive financial market environment through banking policies on Liquidity Management by maintaining the status of liquidity ratios and limits including primary reserve and secondary reserve, Gap Management. by managing and controlling the gap between assets and liabilities to maximize net income margin (NIM), Foreign Exchange Management by maximizing income from differences in foreign exchange rates, Income and Investment Management with high profitability through investment decisions in bank portfolios.